Tinjauan Literatur Penyakit Peyronie Tentang Penanganan Penyakit Peyronie - Muhammad Irfan Hamdi; Exsa Hadibrata (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Peyronie's disease is a sexual disease or medical disorder where the clinical manifestation is penile deformity in the form of penile curvature that occurs in 0.5-20.3% of the male population and is characterized by fibrotic plaques in the tunica albuginea. Aim: To provide information obtained from the literature review process. Methods: Literature search using the keyword 'Peyronie's disease and treatment' in PubMed.